Surface Ligand Management Aided by a Secondary Amine Enables Increased Synthesis Yield of CsPbI3 Perovskite Quantum Dots and High Photovoltaic Performance - Wang, Yao; Yuan, Jianyu; Zhang, Xuliang; Ling, Xufeng; Larson, Bryon W.; Zhao, Qian; Yang, Yingguo; Shi, Yao; Luther, Joseph M.; Ma, Wanli (Advanced materials (Weinheim), 2020)
Lead‐halide perovskite quantum dots (PQDs) or more broadly, nanocrystals possess advantageous features for solution‐processed photovoltaic devices. The nanocrystal surface ligands play a crucial role in the transport of photogenerated carriers and ultimately affect the overall performance of PQD solar cells. Significantly improved CsPbI3 PQD synthetic yield and solar‐cell performance through surface ligand management are demonstrated. The treatment of a secondary amine, di‐n‐propylamine (DPA), provides a mild and efficient approach to control the surface ligand density of PQDs, which has an apparently different working mechanism compared to previously reported surface treatments. Using an optimal DPA concentration, the treatment can simultaneously remove both long‐chain insulating surface ligands of oleic acid and oleylamine, even for unpurified PQDs with high ligand density. As a result, the electrical coupling between PQDs is enhanced, leading to improved charge transport, reduced carrier recombination, and a high power conversion efficiency approaching 15% for CsPbI3‐PQD‐based solar cells. In addition, the production yield of CsPbI3 PQDs can be increased by a factor of 8. These results highlight the importance of developing new ligand‐management strategies, specifically for emerging PQDs to achieve scalable and high‐performance perovskite‐based optoelectronic devices. Di‐n‐propylamine solution in methyl acetate is successfully demonstrated as an efficient solid‐state treatment for CsPbI3 perovskite quantum dot (PQD) solar cells, and a record power conversion efficiency of ≈15% and high reproducibility are achieved for CsPbI3 PQD solar cells.